Understanding the antioxidant and carbonyl sequestering activity of carnosine: direct and indirect mechanisms. (3rd April 2021) - Aldini, Giancarlo; de Courten, Barbora; Regazzoni, Luca; Gilardoni, Ettore; Ferrario, Giulio; Baron, Giovanna; Altomare, Alessandra; D'Amato, Alfonsina; Vistoli, Giulio; Carini, Marina
Abstract: Carnosine is an endogenous dipeptide whose oral administration has been found to prevent several oxidative based diseases including lung disease, type 2 diabetes and its micro and macrovascular complications, cardiovascular disorders, neurodegenerative and kidney disease. While it is generally accepted that the beneficial effects of carnosine are due to its antioxidant, anti-advanced glycation end product (AGE) and -advanced lipoxidation end product (ALE) and anti-inflammatory properties, the molecular mechanisms explaining such effects have not yet been clearly defined. Studies indicate that carnosine acts by a direct antioxidant mechanism and by sequestering reactive carbonyls (RCS), the byproducts of lipid and glucose oxidation, thus inhibiting AGE and ALE which are the reaction products of RCS with proteins. Moreover, carnosine has also been found to act indirectly by activating the Nrf2 transcription factor, a mechanism that would explain many of the effects evoked by this peptide such as anti-inflammatory, antioxidant, antiglycation and anti-carbonyl effects and taken together would explain its therapeutic effect. The present review reports and discusses the most recent studies on the molecular mechanisms of carnosine which need to be fully clarified before promoting carnosine and derivatives as therapeutic agents.